TINGKAT PENGETAHUAN PENGGUNAAN OBAT BENTUK SEDIAAN SUPPOSITORIA PADA MASYARAKAT DESA LANGKAP KECAMATAN BESUKI KABUPATEN SITUBONDO (Periode Februari 2021) - Zuanta Pangestuti (AFAMEDIS, 2021)
Knowledge is information or information that is known or realized by someone. Community knowledge is the result of knowing and this occurs after people have sensed a certain object. The purpose of this study was to determine the level of knowledge of the use of suppository dosage forms in the community of Langkap Village, Besuki District, Situbondo Regency. This type of research is descriptive research with analytical observational method with the sampling technique used in this research is purposive sampling. The measuring instrument used in this study was a questionnaire distributed to 45 respondents with criteria for the age of 15-49 years. Based on the results of the research "Level of Knowledge of the Use of Suppository Drugs in the Langkap Village Community, Besuki District, Situbondo Regency (February 2021 Period)" the results of the percentage level of knowledge for each question were obtained in the categories of knowing, understanding and application domains. The results of the overall level of knowledge obtained are as follows, namely for the tofu category category of 83.40% which is included in the good category, in the understanding domain it is 77.40% which is included in the good category, while in the application domain category it is 80.37% which is included in the good. Keywords : knowledge, society, suppository medicine